Preoperative pad usage is independently associated with failure of non-adjustable male trans-obturator slings in otherwise well-selected patients - Zemp, Logan; Tong, Stephen; Hoy, Nathan; Rourke, Keith F. (Canadian Urological Association Journal, 2018)
Introduction: Our objective was to determine which clinical factors are associated with failure to achieve continence after nonadjustable trans-obturator sling in otherwise well-selected men undergoing treatment for post-prostatectomy incontinence (PPI). Methods: A retrospective review of AdVance/AdVanceTM XP male sling procedures was performed from December 2006 to May 2017. Patients with known risk factors for sling failure, including severe incontinence (>5 pads), radiation therapy, or detrusor dysfunction, were excluded. The primary outcome was failure to achieve continence, defined as ≤1 pad per day when pad use was ≥2 preoperatively (or 0 pads if preoperative pad use was 1). Covariates included patient age, Charlson comorbidity index (CCI), diabetes, obesity (body mass index [BMI] ≥35), type of prostatectomy, and number of preoperative pads. Descriptive statistics and Cox regression analysis was performed. Results: Of 158 patients, continence was achieved in 82.3% (n=130) with a mean followup of 42.7 months. Patient-reported satisfaction was 86.7% (n=137) and the 90-day complication rate was 12% (n=19). On univariate Cox regression analysis, increasing age (p=0.02), CCI (p=0.02), and preoperative pad use (p<0.0001) were associated with sling failure, whereas obesity (p=0.95), diabetes (p=0.49), and type of prostatectomy (p=0.88) were not. On multivariate analysis, only increasing preoperative pad use remained associated with sling failure (hazard ratio [HR] 1.3; 95% confidence interval [CI] 1.1–16; p=0.008). Patients wearing >3 pads per day were more likely to experience failure (35.5% vs. 13.4%; p=0.007). Conclusions: Increasing preoperative pad use is independently associated with an increased risk of failure after non-adjustable sling for post-prostatectomy incontinence in otherwise well-selected patients.